Extracellular Vesicles That Herald the Scarcity of Oxygen - Sekyung Oh; Sang-Ho Kwon (Karger Publishers, 2022)
The natural, membrane-bound nanoscale particles, called extracellular vesicles (EVs) have emerged as an effective, versatile vehicle to transport desired drugs specifically to injury sites. Heralding the presence of the scarcity of oxygen, EVs produced from the cells upregulating the expression of the critical transcriptional regulator of hypoxia, HIF-1, can induce a response in ischemia-reperfusion-damaged cells to ameliorate renal tubular injury and inflammation.